2019
DOI: 10.1021/acschembio.8b01125
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Atypical Tetracycline Formation in Amycolatopsis sulphurea for the Production of Modified Chelocardin Antibiotics

Abstract: To combat the increasing spread of antimicrobial resistance and the shortage of novel anti-infectives, one strategy for the development of new antibiotics is to optimize known chemical scaffolds. Here, we focus on the biosynthetic engineering of Amycolatopsis sulphurea for derivatization of the atypical tetracycline chelocardin and its potent broad-spectrum derivative 2-carboxamido-2-deacetyl-chelocardin. Heterologous biosynthetic genes were introduced into this chelocardin producer to modify functional groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 41 publications
1
26
0
2
Order By: Relevance
“…The chdAR cassette (encoding efflux pump ChdR, its regulator ChdA, and an operator/promoter region) was deleted from A. sulphurea Δ chdPKS mutant [ 46 ], which does not produce CHD. For that purpose, two 1 kb homology cassettes for deletion of chdAR via homologous recombination (primer pairs chdARLF/chdARLR and chdARRF/chdARRR listed in Table S9 ) were cloned via Sph I and Eco RI into plasmid pNV18 [ 78 ], which was transformed into A. sulphurea Δ chdPKS according to previously described protocols [ 26 , 46 ]. In a selected transformant, the deletion of chdAR was identified by colony PCR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chdAR cassette (encoding efflux pump ChdR, its regulator ChdA, and an operator/promoter region) was deleted from A. sulphurea Δ chdPKS mutant [ 46 ], which does not produce CHD. For that purpose, two 1 kb homology cassettes for deletion of chdAR via homologous recombination (primer pairs chdARLF/chdARLR and chdARRF/chdARRR listed in Table S9 ) were cloned via Sph I and Eco RI into plasmid pNV18 [ 78 ], which was transformed into A. sulphurea Δ chdPKS according to previously described protocols [ 26 , 46 ]. In a selected transformant, the deletion of chdAR was identified by colony PCR.…”
Section: Methodsmentioning
confidence: 99%
“…[ 19 ], these gaps were further closed by generating the more potent lead molecule CDCHD [ 15 ]. The chemical space of both compounds has been further extended in recent studies by biosynthetic engineering and medicinal chemistry approaches to explore the structure–activity relationships of these scaffolds [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chelocardin, which was investigated in a phase II clinical trial in 1977, is active against tetracycline-resistant pathogens 41 . The biosynthetic gene cluster of Amycolatopsis sulphurea was recently engineered for the synthesis of derivatives 58 . The dual mode of action of chelocardin was first described based on proteome profiling 22 .…”
Section: Proteomic Profiling Of Trans-translation Inhibitorsmentioning
confidence: 99%
“…In the recent years, we have demonstrated that modifications of CHD through genetic engineering of its producer, the actinomycete A. sulphurea, are not only possible but yielded even more potent antibiotics than CHD itself, like 2-carboxamido-2-deacetyl-chelocardin (CDCHD) [8]. Our work also provided an understanding of the structure-activity relationship of CHD [9]. Furthermore, CDCHD was semi-synthetically modified [9,10] with the aim to optimize the potent CHD derivative even further.…”
Section: Introductionmentioning
confidence: 82%
“…Our work also provided an understanding of the structure-activity relationship of CHD [9]. Furthermore, CDCHD was semi-synthetically modified [9,10] with the aim to optimize the potent CHD derivative even further.…”
Section: Introductionmentioning
confidence: 92%